Effect of Job Training and Motivation on Employee Performance with Competency as Mediator at PT PLN (Persero) West Sumatra Main Distribution - rizal, Das; Indrayani, Tri Irfa; Adie Irwan (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2026)
Employee performance is a critical factor in organizational success and is influenced by various psychological and behavioral factors. Among them, work motivation and job satisfaction play significant roles in shaping employee behavior and outcomes. However, the role of competency as mediating variable in this relationship has not been thoroughly explored. This study aims to identify and analyze the influence of job training and motivation on employee performance, with competency serving as a mediating variable. This research uses a quantitative approach, involving 184 employees selected through probability sampling. Data were collected using a structured questionnaire and analyzed using Partial Least Squares-Structural Equation Modeling. The results indicate that job training not has direct effect (P = 0.207). However motivation (P = 0.001) has a direct, significant effect on employee performance. Likewise, job training (P = 0.040) and motivation (P = 0.000) has a direct influence on competency. Competency has a significant impact on performance (P = 0,000), and it mediates the effect of job training (P = 0.049) and motivation (P = 0.000) on employee performance. Competency plays a crucial mediating role in translating job training into improved employee performance